Development of Rational Rail Network Topology for High-Speed and Conventional Trains Based on Bacterial Foraging Optimization - Panchenko, Sergii; Butko, Tatyana; Prokhorchenko, Ðndrii; Parkhomenko, Larisa; Zhurba, Oleg (International Journal of Engineering and Technology, 2018)
Development of projects on higher speeds of passenger trains on the world railways requires investigation into the balanced combination of routes for high-speed and conventional trains considering railway network topology. The objective of the study is consideration of railway network peculiarities regarding transportation demand by designing a mathematical model to find an optimal passenger train flow distribution. In order to formalize the process of a simultaneous search for the rail passenger network topology and determination of the most probable distribution within the formed train flow network for high-speed and conventional trains it has been proposed to use a criterion as a system entropy adapted to the rail passenger-oriented transportation. The concept of entropy is based on isomorphism in systems, which allows monitoring and implementing the link between a micro and macro level in the passenger transportation system. To solve the mathematical model the authors have used an optimization method based on Bacterial Foraging Optimization (BFO). The implementation of the mathematical model based on BFO will make it possible to theoretically substantiate the efficiency of existing and promising projects on higher speeds of passenger trains on the rail transport regarding adaptation of the network topology to transportation demand.Â Â